Skopos Theory and The French Adaptation of The Palm-Wine Drinkard as L'Ivrogne dans la Brousse. - Ogbeide-Ihama, Mojisola A. (Àgídìgbo: ABUAD Journal of the Humanities, 2014)
Taking a functionalist approach to translation, translators choose their translation strategies according to the purpose or function the translated text is intended to fulfill for the target audience. This paper attempts to interrogate the application of Skopos-theory concepts to the adaptation of The Palm-Wine Drinkard and his Dead Palm-Wine Tapster in the Deads ' Town by Amos Tutuola as L 'ivrogne dans la brousse by Raymond Queneau. It also aims at proving the possibility of translating a text according to a specific objective. In order to facilitate our discussion, we will use the Skopos theory in analysing the French version of The Palm- Wine Drinkard. This paper concludes that some elements of Skopos theory were made manifest in the adaptation of The Palm-Wine Drinkard and that the translation of the novel was made by the standards of Skopos theory.